Mechanical behaviour of sandy soils embankments treated with cement and reinforced with discrete elements (fibres) - Mohamed Bouteben Yasmine; Boudaoud Zeineddine (Fracture and Structural Integrity)
It is well known that chemical treatment with cement and reinforcement with polypropylene fibres are considered as a solution to soil stability problems. This technique ameliorates the mechanical and physical comportment of the soil. Based on this, this research paper aims at investigating the mechanical behaviour of a specific type of dried-cemented-sandy soil reinforced with discrete elements such as polypropylene fibre basically through experimental tests. The latter is a series of consolidated drained triaxial tests which were carried out on sand samples that are prepared with 0, 3 and 6% of cement, reinforced with 1% of polypropylene fibre (12, 18 mm) randomly distributed. Furthermore, those contents are measured by the volume of dry sand. In addition to these tests, the mechanical properties of two types of reinforced sand obtained experimentally, were used in a numerical analysis of a road embankment using a finite element program such as Plaxis 2D in order to observe the variation of different parameters like safety factor and the displacements (Ut, Ux, Uy). The test results showed that the addition of cement and polypropylene fibre of different accommodations increased both cohesion and friction angle of sands while the numerical results indicated that the presence of these additions improved the safety factor and decreased significantly the displacements.